Post transcatheter aortic valve replacement ejection fraction response is predictor of survival among patients with whole range of systolic dysfunction. Issue 5 (16th July 2021) - Kilicaslan, Baris; Unal, Baris; Coskun, Mehmet Sait; Zeren, Gonul; Ekin, Tuba; Ozcan, Sevgi; Erdogan, Sıddık; Ozdemir, Emre; Deniz, Orsan; Ertas, Faruk; Karabay, Can Yucel; Kaya, Dayimi; et al.
Abstract: Aims: The objective of this study is to assess the prognostic effects of T ranscatheter aortic valve replacement (TAVR) on the patients with different degrees of left ventricular systolic (LVS) function and severe symptomatic aortic stenosis. Also examines the prognostic association of LV remodelling after TAVR. Methods and results: Patients stratified into four subgroups with respect to baseline LV ejection fraction (LVEF) (LVEF > 25%, LVEF 25%–40%, LVEF 41%–49% and LVEF ≥ 50%). We compared the baseline characteristics and temporal changes in echocardiographic parameters of the patients after TAVR, and determined all-cause mortality (ACM) in a follow-up period of mean 20.7 ± 15.8 months (up to 84). There were 495 patients at 8 centres. ACM was similar in all groups (28.1%, 29.5%, 22.5% and 24.1% respectively; p   =  .44). Immediately after TAVR, there was an improvement in LVEF (from 38.7 ± 9.4 to 44.9% ± 10.9%, p   <  .001). The percent change in LVEF (pDelta-EF) immediately after TAVR was more prominent in the patients with LVEF < 25% (48.1 ± 49.6, 21.9 ± 29.6), (8.4% ± 15.2%) and (2.1 ± 7)) ( p   <  .01). Importantly, a 12% increase in absolute Delta-EF was observed in patients with LVEF< 25% with 100% sensitivity and 42.5% specificity for the prediction of ACM. Conclusion: This study shows that TAVR is beneficial in the whole range of LVS function, irrespective of the baseline EF. Early recovery in LVEF after TAVR is critical for survival, however, it seems to be more eye catching in the patients with advanced heart failure with reduced EF.